2019
DOI: 10.3390/ijerph17010186
|View full text |Cite
|
Sign up to set email alerts
|

Breastfeeding and the Risk of Infant Illness in Asia: A Review

Abstract: Infancy remains the most vulnerable period of human life for death, illness, and establishing a lifetime trajectory of growth and health. It is estimated that there are 5.3 million deaths under five years of age worldwide and approximately 800,000 lives could be saved by improving breastfeeding rates and duration. In Asia, an estimated 300,000–350,000 child deaths could be prevented with optimal breastfeeding and the majority would be under 12 months of age. We present a systematic review of studies of infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(41 citation statements)
references
References 105 publications
0
36
0
Order By: Relevance
“…Breastfeeding is known to provide both short-term and long-term benefits to infants, mothers and the society in general [ 1 , 2 ]. Both the World Health Organization (WHO) and the Chinese Ministry of Health recommend that infants should be exclusively breastfed for the first 6 months of life to achieve optimal growth, development and health [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Breastfeeding is known to provide both short-term and long-term benefits to infants, mothers and the society in general [ 1 , 2 ]. Both the World Health Organization (WHO) and the Chinese Ministry of Health recommend that infants should be exclusively breastfed for the first 6 months of life to achieve optimal growth, development and health [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mothers will be excluded if they meet any of the following criteria: being referred from other hospitals for high-risk pregnancy treatments; receiving advice from doctors against breastfeeding because of her health condition (e.g., positive T-cell lymphotropic virus, untreated brucellosis, varicella, H1N1 influenza) [ 111 ]; where an infant is born with a birth weight of less than 2500, or is admitted to neonatal intensive care unit, the mother will continue receiving information from the app, but will be excluded from the analysis; if the infant has any of the infections or metabolic conditions as advised by the WHO or the Ministry of Health, where breastfeeding is contraindicated [ 11 , 112 ]. …”
Section: Methodsmentioning
confidence: 99%
“…There are around 5 million deaths annually of children under 5 years of age and it is estimated that increasing breastfeeding rates to recommended levels could save 823,000 children’s lives annually [ 1 ]. A recent review confirmed the importance of breastfeeding in protecting against many infections; compared to infants given formula, there are significantly lower rates of diarrhoeal disease and lower respiratory tract infection, with a reduction of 50% or more to be expected, especially in infants under six months of age [ 11 , 12 ]. Exclusive breastfeeding is important for establishing a healthy microbiome, which has an important protective effect against chronic disease later in life, including obesity [ 13 , 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…According to the World Health Organization, mothers should breastfeed infants exclusively for at least 6 months [1]. Infants benefit from breastfeeding, both in the short-term in terms of a reduced incidence and mortality rate of infectious diseases and in the long-term in terms of a reduced risk of adult obesity, diabetes, cardiovascular disease, and other metabolic diseases [2][3][4].…”
Section: Introductionmentioning
confidence: 99%